The Interplay between Presidential Democracy, Federalism, and the Push for Political Restructuring in Nigeria - Musa, Auwalu; Bayero, Abdullahi Ado; Bappah, Fatima; Muhammed, Zakari Zakariyya; Ibrahim, Ayuba; Auta, Rebecca Shekwonya (Kashere Journal of Politics and International Relations, 2024)
Federalism initially conceived to accommodate Nigeria's diversity, grapples with challenges such as centralization, power imbalances, and governance issues, prompting a reevaluation of its structure. A static approach to federalism has proven ineffective, highlighting the need for a dynamic process that evolves through negotiation, adaptation, and consensus-building. This study utilizes qualitative data collected from secondary sources, including books and journal articles, to explore the intricate relationship between presidential democracy, federalism, and the push for political restructuring in Nigeria. The analysis reveals that democracy and federalism share commonalities with the doctrine of Separation of Powers, operating based on established rules and processes. However, certain undemocratic elements, such as concerns about local government autonomy, perceived biased appointments, growing insecurity, and campaign strategies, contribute to the clamor for political restructuring. The study concludes that a fundamental shift is necessary, emphasizing the devolution of power, resources, and responsibilities from the central government to states. This decentralization can effectively address grievances related to resource allocation and enhance regional autonomy. Furthermore, revisiting historical regional structures or considering a two-tier system involving the federal government and states, potentially subsuming local government areas under the states, could promote better governance and resource management at the regional level